Differences in exercise intensity seems to influence the affective responses in self-selected and imposed exercise: a meta-analysis - Oliveira, Bruno; Deslandes, Andréa; Santos, Tony (Frontiers in Psychology, 2015)
Self-selected exercise seems to promote positive affective responses due to the perceived autonomy associated with it. The objective of the present study was to determine the magnitude of differences in Feeling Scale (FS) responses during self-selected and imposed exercise sessions. The PRISMA Statement was adopted for this meta-analysis. The search used PubMed, Scopus, PsycINFO, and ISI Web of Knowledge databases. A total of 10 studies that compared the effects of self-selected and imposed exercise sessions on acute FS responses were included. The screening strategy included: exclusion of studies that were duplicated between databases, abstract screening, and text screening. The standardized mean difference (SMD) between self-selected and imposed exercise sessions categorized in five intensities (equal intensity: both exercises were performed at the same intensity, below lactate/ventilatory threshold (LT/VT): imposed exercise was performed at an intensity below the LT/VT, at LT/VT: imposed exercise was performed at the LT/VT intensity, above LT/VT: imposed exercise was performed at an intensity above the LT/VT, and different intensity: both exercises were performed at different intensities and the intensity of imposed session was not reported relative to LT/VT) and an overall SMD were calculated. Self-selected exercise was used as the reference condition. The subtotal SMD values were as follows: -.10 (equal intensity), -.36 (below LT/VT), -.57 (at LT/VT), -1.30 (above LT/VT), and -.09 (different intensity). The overall SMD was -.41. These results have shown that the differences in the exercise intensity used in imposed exercise sessions influenced the affective responses considering that higher intensities of imposed session provided higher effect size in favor of self-selected exercise.